Are SiO molecules the seed of silicate dust around evolved stars?. Issue Volume 15:Issue S350(2019) (April 2019) - Jiang, Biwei; Liu, Jiaming
Abstract: Silicate is the most popular dust species in the circumstellar envelope of evolved oxygen-rich stars, yet its seed particles have not been well identified. Among the candidates, corundum and SiO attract intense attention and study. SiO was suggested to be the seed particles in early 1980s and has received various supports as well as oppositions. In this work we investigate the relation of SiO maser and silicate dust emission powers. With both our own observation by using the PMO/Delingha 13.7-m telescope and the archival data, a sample is assembled of 21 SiO v=1, J=2-1 sources and 28 SiO v=1, J=1-0 sources that exhibit silicate emission features in the ISO/SWS spectrum. The analysis of their SiO maser and silicate emission power shows a moderate correlation, which agrees with the idea that SiO molecules are the seed nuclei of silicate dust.